Meningkatkan Motivasi Belajar Melalui Penerapan Culturally Responsive Teaching Dalam Pembelajaran - Willenda, Zilvira; Yantoro, Yantoro; Misnawati, Misnawati; Basyir, Basyir (LP2M Universitas Islam Ahmad Dahlan, 2024)
This study aims to investigate the effectiveness of implementing the Culturally Responsive Teaching (CRT) approach in increasing the learning motivation of grade 4 students of SDN 42/IV Jambi City in Indonesian language learning. Using classroom action research (PTK), data was collected through direct observation of students' learning activities over three cycles, as well as a learning motivation questionnaire completed by 28 students. Results showed that at the beginning of the study, only 21.4% of students had high learning motivation, 35.7% with moderate motivation, and 42.9% with low motivation. Through the application of CRT, students' participation and engagement in learning increased significantly. In the last cycle, the average score of students' learning motivation increased from 58 to 76, reflecting an overall increase in students' learning motivation. These results indicate that the CRT approach is effective in stimulating students' learning motivation. The findings emphasize the importance of paying attention to students' cultural context in designing effective and relevant learning strategies, as well as the need to strengthen teachers' capacity in implementing CRT in the classroom. By utilizing students' cultural backgrounds, teachers can create an inclusive and motivating learning environment.